Migration Policy of Kazakhstan: Overview of External Vector (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
This article aims to provide an analysis of the external aspects of Kazakhstan’s post-pandemic migration policy through the prism of evolving domestic legislation and expert assessments. Kazakhstan is becoming an increasingly important actor in migration processes in Central Asia and in the CIS generally.The continual transformation of the region during the three decades since independence has accelerated and diversified migration within Central Asia and beyond the region. The effects of migration also significantly affect Kazakhstan, which has a diversified migration profile and regularly positions itself as a country of reception and transit.  Additionally, there is an observable outflow of the young and able-bodied population. This situation requires the adoption of appropriate policies and approaches to meet the challenges and realities of migration.This article examines the main approaches of the government of Kazakhstan to the development and implementation of its migration policy through the lens of the major trends of external migration. Its main emphasis is migration policy in relation to the regulation of the stay of foreign citizens within the nations of Central Asia and the CIS, for whom a visa-free regime exists. These foreign arrivals are mostly labor migrants. The categorization of such migrants as refugees and asylum seekers in Kazakhstan is considered.The methodology used in the article a survey of experts and analysis of legislation. The results of this research bring into focus the evolving legislation in the field of migration and diversification of migration policy in Kazakhstan in accordance with current trends and changes to the situation along the border.Furthermore, an exploration of available resources on the subject reveals that greater attention is required to such aspects as an increasing proportion of female migrants, forced migration,  and irregular migration patterns.Key words: Migration policy, Kazakhstan, labor migration, refugee rights, “Otandastar Foundation (Qory)”.